Assessment of ellagic acid action in 5-fluorouracil induced intestinal mucositis - Dareen Al-hoshary; Munaf H. Zalzala (Iraqi Journal of Pharmaceutical Sciences, 2023)
The intestinal mucositis define as inflammation and ulceration in the gastrointestinal tract wall and in some case in the oral cavity these cause by treatment with antineoplastic drug like 5-fluorouracil and Irinotecan and other types of chemotherapeutics drugs , 5-Fluorouracil-induced intestinal mucositis (IM) is consider as one of the more common tumor issue .it cause series of undesirables symptoms like severe diarrhea ,abdominal pain , stomach uncomfortable and other. The aim of this current study to see how ellagic acid act to  Attenuates 5-FU-Induced Intestinal Mucositis and  Diarrhea in Mice . we induced the intestinal mucositis by injected the mice intraperitoneally in 5-fluorouracil about 50mg per kg daily for four days respectively and then assessment the IM by measurement the level of some antioxidant enzymes like SOD , and level of some pro-inflammatory cytokines (IL-6) and lipid peroxidation biomarker (MDA) and we note the difference in the histopathological scoring after administration the ellagic acid to the mice in two different dose (10mg and 5mg per kg) daily for ten days respectively and before the fluorouracil injection  in one hour .pretreatment with ellagic acid specialized dose of 10mg per kg significant improvement in the level of antioxidant enzymes ,pro inflammatory cytokines ,lipid peroxidation biomarker and histopathologicaL score  compared with 5-FU group, moreover the potential action of ellagic acid was further supported by histopathological examination. all these data suggest that the ellagic acid effective in protective from 5-FU-induced intestinal mucositis.